23.1k views
0 votes
Hi, can you help me to solve this problem please!

Hi, can you help me to solve this problem please!-example-1
User Niaz
by
5.2k points

1 Answer

5 votes

Replace the expression -u-5 for z into the rule of correspondence of h to find h(-u-5):


\begin{gathered} h(z)=z^2 \\ \Rightarrow h(-u-5)=(-u-5)^2 \end{gathered}

Expand the square binomial using the formula (a+b)^2=a^2+2ab+b^2, with a=-u and b=-5:


\begin{gathered} (-u-5)^2=(-u)^2+2(-u)(-5)+(-5)^2 \\ =u^2+10u+25 \end{gathered}

Therefore:


h(-u-5)=u^2+10u+25

User John Prado
by
5.2k points